Determinants of vaccination behavior among university students 20 months after the COVID-19 outbreak: Results of the COVID-19 German Student Well-being Study (C19 GSWS) - Jannis Trümmler; Eileen Heumann; Stefanie M. Helmer; Heide Busse; Christiane Stock; Sarah Negash; Claudia R. Pischke (Taylor & Francis Group, 2022)
Evidence indicates a higher COVID-19 vaccine hesitancy among university students due to their age and a lower risk of COVID-19 related complications compared to the general population in Germany. However, little is known about the other determinants of COVID-19 vaccination behavior for the population of German university students. This study aimed to investigate determinants of vaccination behavior in this population. The cross-sectional COVID-19 German Student Well-being Study was conducted at five German universities from October 27th to November 14th, 2021, via an online survey (n=7,267). Multiple logistic regressions were calculated to examine associations of psychological antecedents of vaccination (5Cs: confidence, complacency, constraints, calculation, collective responsibility), Critical Health Literacy in a Pandemic (CHL-P), and additional determinants (previous infection, trust in the health care system, feeling informed about the COVID-19 vaccine) and vaccination status (not vaccinated vs. fully vaccinated). All 5Cs were associated with reporting to be vaccinated, except for complacency. Regarding the CHL-P, students who felt that the current scientific knowledge about COVID-19 in terms of the policy decisions on pandemic measures was very complex had higher odds for reporting being vaccinated (OR=3.02; 95% CI: 2.26-4.04). Students who felt well informed about the COVID-19 vaccines were also more likely to report being fully vaccinated (OR=2.20; 95% CI: 1.51-3.21). Due to our finding that the 5Cs are associated with vaccination status among university students, we recommend that the different components of the 5Cs should be considered in future vaccination campaigns implemented in the university context.